Research on top-level planning for sustainable high-quality development of China’s largest scale deep coal mining area - Xin, Delin; Li, Chen; Chen, Tuantuan; Fang, Xinying; Zhao, Qiang; Chen, Hu (Frontiers in Earth Science, 2023)
Coal is the dominant energy source in China, as it has an advantageous position in terms of resource distribution. Against the backdrop of China’s high-quality economic development and the global energy crisis, after nearly a decade of preparation, the Xinjie Taigemiao Mine Area (XTMA) has entered the substantial planning and design stage. Based on the resource development conditions and the background of the times of XTMA, the paper provides an in-depth analysis of the connotation and characteristics of XTMA’s high-quality development. Subsequently, the overall development concept of “1358” for XTMA is proposed, which includes one strategic objective, three new models, five attribute goals, and eight assessment indicators. Based on this, a top-level planning and design for the implementation of high-quality development in XTMA is carried out comprehensively from aspects such as spatial layout, intelligent safety, integrated zero-carbon, ecological green, technological innovation, cluster management, and harmonious happiness. Finally, we look forward to the long-term blueprint for high-quality development of the XTMA and put forward urgent recommendations for current construction. The research on the high-quality development plan of XTMA will promote the development of China’s coal industry and is of great significance.